(untitled) (MMIT Proceedings, 2025)
The article examines the role of the head as a leader of the professional teaching community (PTC), analyzing theoretical approaches to leadership within the educational environment. Special attention is given to the managerial functions that foster the development of a professional culture of collaboration, enhance motivation, and promote the implementation of innovative practices in education.